The day the crayons quit ebook - Daywalt, Drew (2014)
The hilarious, colorful #1 New York Times bestselling phenomenon that every kid wants! Gift a copy to someone you love today. Poor Duncan just wants to color. But when he opens his box of crayons, he finds only letters, all saying the same thing: His crayons have had enough! They quit! Blue crayon needs a break from coloring all those bodies of water. Black crayon wants to be used for more than just outlining.  And Orange and Yellow are no longer speaking—each believes he is the true color of the sun. What can Duncan possibly do to appease all of the crayons and get them back to doing what they do best? With giggle-inducing text from Drew Daywalt and bold and bright illustrations from Oliver Jeffers, The Day the Crayons Quit is the perfect gift for new parents, baby showers, back-to-school, or any time of year! Perfect for fans of Don't Let the Pigeon Drive the Bus by Mo Willems and The True Story of the Three Little Pigs by Jon Sciezka and Lane Smith.  Praise for The Day the Crayons Quit: Goodreads’ 2013 Best Picture Book of the Year Winner of the E.B. White Read-Aloud Award * “Hilarious . . . Move over, Click, Clack, Moo ; we’ve got a new contender for the most successful picture-book strike.” – BCCB , starred review “Jeffers . . . elevates crayon drawing to remarkable heights.” – Booklist “Fresh and funny.” – The Wall Street Journal "This book will have children asking to have it read again and again.” – Library Media Connection * “This colorful title should make for an uproarious storytime.” – School Library Journal , starred review * “These memorable personalities will leave readers glancing apprehensively at their own crayon boxes.” – Publishers Weekly , starred review “Utterly original.” – San Francisco Chronicle